Model Pemberdayaan Ekonomi Santri Berbasis Digital Entrepreneurship melalui Pelatihan TikTok Seller di Lingkungan Pesantren - M Ario Akbar; M Arif Musthofa; Al-Munip (SiNORA, 2025)
This study aims to analyze the model of santri economic empowerment through digital entrepreneurship training based on the TikTok Seller platform within the pesantren environment. The initiative is motivated by the importance of enhancing the entrepreneurial competencies of santri in responding to the increasingly competitive digital economy era. The research employs a Participatory Action Research (PAR) approach, involving santri as active participants in all stages of the program, including training, mentoring, and the practical implementation of online selling through TikTok Seller accounts. Data were collected through observation, interviews, and documentation, and analyzed using a descriptive qualitative method. The findings indicate that the training successfully improved the santris’ digital literacy, managerial abilities, and economic independence. Furthermore, the program fostered the development of an entrepreneurial ecosystem within the pesantren that is adaptive to technological advancement. The resulting empowerment model consists of three key stages: digital literacy, marketing content management, and online business practices grounded in Islamic values. Therefore, the TikTok Seller training proved to be an effective strategy for santri economic empowerment through digital entrepreneurship, aligning with contemporary socioeconomic demands